COVID-19 and ASEAN responses: Comparative policy analysis. (December 2020) - Djalante, Riyanti; Nurhidayah, Laely; Van Minh, Hoang; Phuong, Nguyen Thi Ngoc; Mahendradhata, Yodi; Trias, Angelo; Lassa, Jonatan; Miller, Michelle Ann
Abstract: Scholars and policy-makers agree that cross-border and multi-sector cooperation are essential components of coordinated efforts to contain the spread of COVID-19 infections. This paper examines the responses of ASEAN (Association of Southeast Asian Nation) member countries to the COVID-19 pandemic, including the limits of regional cooperation. ASEAN has pre-existing cooperative frameworks in place, including regional health security measures, which, at least theoretically, could assist the region's efforts to formulate cooperative responses to containing a global pandemic. With its overarching "One Vision, One Identity, One Community", ASEAN cooperation has extended to include region-wide disaster responses, framed as "One Asean, One Response". Using content analysis, this paper examines media statements and policies from ASEAN member states and the ASEAN Secretariat to assess the collective response to COVID-19 during the period from January to August 2020. By identifying gaps and opportunities in government responses to COVID-19 as the virus spread throughout Southeast Asia, this paper provides new insights as well as recommendations for the future.